CONCEPTUALIZING PARENTING IN AN INSTITUTIONAL CONTEXT: THE ROLE OF PERSONAL ATTACHMENT HISTORY - Petrova, Sevdalina (E-Journal VFU, 2025)
This article examines the impact of attachment on children and youth in family care settings, correlating with attachment building in the context of Family Type Accommodation Center through caregivers’ internal working models.